Evaluation of Medical School Grading Variability in the United States: Are All Honors the Same?. (December 2019) - Westerman, Mary E.; Boe, Chelsea; Bole, Raevti; Turner, Norman S.; Rose, Steven H.; Gettman, Matthew T.; Thompson, R. Houston
Abstract : Purpose: The medical student performance evaluation (MSPE) summarizes a residency applicant's academic performance. Despite attempts to improve standardized clerkship grading, concerns regarding grade inflation and variability at United States medical schools persist. This study's aim was to describe current patterns of clerkship grading and applicant performance data provided in the MSPE. Method: The authors evaluated Electronic Residency Application Service data submitted to a single institution for the 2016–2017 Match cycle. Clerkship grading characteristics regarding grading tiers, school rank, location, and size were obtained. Data regarding methods for summative comparisons such as key word utilization were also extracted. Descriptive statistics were generated, and generalized linear modeling was performed. Results: Data were available for 137/140 (98%) MD-granting U.S. medical schools. Pass/fail grading was most commonly used during the preclinical years (47.4%). A 4-tier system was most common for clerkship grading (31%); however, 19 different grading schemes were identified. A median of 34% of students received the highest clerkship grade (range, 5%–97%). Students attending a top 20 medical school were more likely to receive the highest grade compared with those attending lower-rated schools (40% vs 32%, P < .001). Seventy-three percent of schools ranked students, most commonly using descriptive adjectives. Thirty-two different adjectives were used. Conclusions: There is significant institutional variation in clinical grading practices and MSPE data. For core clerkships where most students received the highest grade, the ability to distinguish between applicants diminishes. A standardized approach to reporting clinical performance may allow for better comparison of residency applicants. Abstract : Supplemental Digital Content is available in the text.